Red shirt colour is associated with long-term team success in English football - Attrill, M. J.; Gresty, K. A.; Hill, R. A.; Barton, R. A. (Journal of Sports Sciences, 2008)
The colour of sportswear has been shown to influence the outcome of bouts for several different combat sports. The generality of these effects, and whether they extend to collaborative forms of contests (team sports), is uncertain. Since 1947, English football teams wearing red shirts have been champions more often than expected on the basis of the proportion of clubs playing in red. To investigate whether this indicates an enhancement of long-term performance in red-wearing teams, we analysed the relative league positions of teams wearing different hues. Across all league divisions, red teams had the best home record, with significant differences in both percentage of maximum points achieved and mean position in the home league table. The effects were not due simply to a difference between teams playing in a colour and those playing in a predominantly white uniform, as the latter performed better than teams in yellow hues. No significant differences were found for performance in matches away from home, when teams commonly do not wear their "home" colours. A matched-pairs analysis of red and non-red wearing teams in eight English cities shows significantly better performance of red teams over a 55-year period. These effects on long-term success have consequences for colour selection in team sports, confirm that wearing red enhances performance in a variety of competitive contexts, and provide further impetus for studies of the mechanisms underlying these effects.